A jornada do herói: uma proposta audiovisual e interdisciplinar para o ensino de história na educação profissional - Marques, Bruno Ribeiro (2020)
This dissertation discusses the teaching of History with in the Professional Education modality, thinking strategies to promote curricular integration between history and technical disciplines, more precisely in the Audio and Video Production course. When presenting the characteristics of both the modality and the Audio and Video Production course, we will discuss the importance of digital literacy as a form of conscious consumption of information present in the cyberspace. It is also proposed the instrumentalization in history through the study of the concepts of memory, identity and narrative. For this, we will analyze the syllabuses, both national and from the states and how they present these concepts for teaching our science. From the analysis of the syllabuses, we will use historiography to think about the challenges and possibilities of using the terms in question in the teaching of history. After this theoretical exercise, we will start the planning and execution of our product aiming to integrate the teaching of History to technical disciplines. During the process of developing the practices thoughts, 2nd grade students of the State School of Professional Education Jaime Alencar de Oliveira, in the city of Fortaleza -CE were encouraged to write their autobiographies, five were chosen, scripted and turned into films, produced by the technical course students themselves. During the activities carried out with the students, based on active methodologies, concepts of memory, identity and narrative were discussed, which culminated in audiovisuals that can be understood as elements of Public History. Our activity proposed exemplifies a form of curricular integration, the focal point of Curricular Guidelines for the Professional Education modality also contemplating the production of school history knowledge